Stock Price Valuation Analysis Using Free Cash Flow To Equity And Relative Valuation Method Case: Bank Jago Tbk. (ARTO) - Hasbi Ibrahim; Maria Ulpah (Syntax Corporation, 2022)
Purpose – this paper aims to calculate the intrinsic value of ARTO (PT. Bank Jago Tbk.). Design/Methodology/Approach – the stock valuation calculated using free cash flow to equity method and relative valuation method. Findings – based on the calculation, it is expected that the results of the valuation will be below the market value. Practical Implications – the findings may help related parties including investors to consider carefully before deciding their investment on the company. Originality/Value – to the author’s best knowledge, little equity research has been done for digital banking in Indonesia especially on the value of ARTO.